To See the Unseen: From History Books to Learning from the Landscape - Veronika Kupková (Sprawy Narodowościowe. Seria nowa)
The Czech-German borderscape, which has been affected by forced migrations several times over the last hundred years, contains many layers of memory. Some of them can still be identified, while others need to be searched for because their traces have been erased. In this context, this article aims to discuss the possibilities of place-based learning, using a case study from the Ore Mountains: the former town of Pressnitz. The study introduces resources that can be used by educators to promote the understanding of complex processes and global phenomena, such as colonialism, power structures, mobility, globalization, and gender. The analyzed materials include archivalia from Czechia, Germany, and Austria, as well as documents from private collections in various European countries. The existence of regional and global interconnections between the Czech lands (Bohemia) and colonies is surprising, but it can also help educators to support self-identification with the region on a local level through new narratives.